Solar Energy and Technology. - Mijic, Goran (Solar Energy and Technology ;, 2018)
Volume 2 is the most comprehensive and detailed encyclopedia of solar energy and technology available today, containing all essential solar terms in one place. A convenient source for spelling, classifications, and concise definitions of terms encountered in the study, reading, and practice of solar technologies. The scope of the encyclopedia includes all terms of importance and topics of primary significance in the field. As the solar field is one of the fastest growing and changing sectors in the energy industry today, the ambition of this encyclopedia is to cover all key state-of-the-art solar components and technologies, including photovoltaic appliances and systems, solar-thermal systems, nanophotovoltaics, semiconductor materials and technologies, energy storage systems, software applications, solar architecture, measuring devices, units of measurements, mounting systems and components, hybrid power systems, solar occupations, infrastructure, rules and regulations, economics, and much more. Written in a clear, precise, and easy-to-understand style, the encyclopedia is equally accessible to solar specialists and laymen. It is ideal for students, solar enthusiasts, and solar professionals, such as solar technicians, electricians, installers, engineers, scientists, designers, architects, managers, salesmen, marketing specialists, attorneys, writers, and translators. Over 8000 entries used every day in the solar field - Accurate and up-to-date explanations of solar terms that keep the meaning in focus and provide the context in which terms are used Abbreviations and acronyms - Explanation of what they stand for, with links to the complete definitions Synonyms and related concepts - Help users identify words with identical or similar meaning References to related terms - Full cross-referencing between entries widens the semantic scope of terms and provides helpful links for further exploration Illustrations - Provide visual aids, offering additional clarification for complex concepts Names of important solar and sustainable energy organizations